Geração compartilhada a partir do biogás da suinocultura em uma unidade consumidora industrial - Stencel, Willian Felipe (2022)
One of the expenses in the industrial sector is electricity and managing this expense can bring savings to the consumer unit and make it more competitive in the market. This work presented a case study of energy efficiency using shared generation to minimize the expenses in the electric energy bill of a ceramic industry, located in the municipality of Itaipulândia/PR. Analyzes of energy bills were carried out to characterize the demand and consumption of this unit and lifting loads onsite to assess the possibility of changing the time of use of electrical equipment. The theoretical design of a power generation plant from biogas produced on a rural swine farm, located close to the ceramic industry, was also the object of this work. The preliminary technical studies were followed by an analysis of economic indicators to verify the feasibility of shared generation by a consortium between rural property and the ceramic industry. As a result of this research, it was possible to determine the green modality as the best contract between the industry and the distribution concessionaire (green time). The preliminary study showed the need for a BLCtype biodigester with 1,947 m³ and a 50 kVA engine generator set at an estimated total cost of R$ 408,425.55. With the shared generation credits, it was possible to estimate an annual cost reduction in the electricity bill of approximately R$ 58,131.24 (13.61%), which could make the company more profitable and competitive in the market. Among the conclusions, it is highlighted that the handling of the animal substrate for the generation of electric energy and biofertilizer material in the rural property can be a sustainable and viable business.